Edukasi Penerapan Terapi Bermain Puzzle Sederhana Untuk Perkembangan Motorik Halus Pada Anak Usia 3-6 Tahun Di UPT Puskesmas Kedaton Bandar Lampung - Setiawati Setiawati; Aryanti Wardiyah; Linawati Novikasari; Dewi Kusumaningsih; Eka Yudha Chrisanto; Andi Bunga Silvia; Dian Angen Saputra; Tiya Nadila; Restiana Cahyani; Mutiara Ayu Daniati; Herliza Herliza; Marlena Marlena; Partur Khorip (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Fine motor skills are movements carried out by the fingers with a central nervous cell arrangement that regulates the use of small muscle groups such as the fingers and hands, and often require precision and coordination with the hands. One type of game that can optimize children's fine motor development is puzzle games. Puzzles are a type of game that improves thinking skills, makes it easier to remember and understand concepts, and increases creativity. Puzzle games are simple games that are played in pairs and require precision because children are trained to focus their minds so they can concentrate. The aim of this activity is to improve fine motor development in children through puzzle play therapy. It was found that respondents were very enthusiastic about carrying out play therapy. The conclusion from this activity is that fine motor development in children can be trained using puzzle play therapy.